The elderly: A foreign land - Bonavita, Viviana; Brescia, Filomena; Sacchi, Simona (Quaderni di Psicologia Clinica, 2023)
This work aims to investigate what the demand of the elderly is. Common sense persists in seeing elderly people as only needing assistance, security and medical care. In reality they are an unknown land, a foreign land, about which we can know more if we do not give up learning about their experiences. From the reports of the interventions that will be presented, in particular from an intervention at a nursing home, it becomes clear how we can expect from the elderly a relationship in which emotions can be explored, recognising the vitality of people's inner world even at a late age. The experience of the elderly is not only depression and anticipation of death; even when thinking about death, one can do so in a very emotional and unpredictable way. Another possible area of intervention is to mend the relationship between families, the elderly and the services dedicated to them.
Keywords: nursing home; emotions of the elderly; clinical psychological intervention with the elderly; non-self-sufficiency.